2017
DOI: 10.5414/cp202796
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of flucloxacillin and its metabolites in patients with renal failure: Impact on liver toxicity

Abstract: Based on data from perfused rat livers, high biliary concentrations of 5-OH-FX might also be observed in our patients explaining why LDH, bilirubin, and alkaline phosphatase were elevated in up to 8/12 patients after repeated infusion of flucloxacillin. Liver toxicity of flucloxacillin might therefore be observed in patients with renal impairment after continuously elevated 5-OH-FX levels.
.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The mass increase of 18 relative to flucloxacillin (m/z 454.059) indicates that this product most likely corresponds to the penicilloic acid formed by hydrolysis of the β‐lactam ring of flucloxacillin which is not dependent on CYP‐activity. The penicilloic acid of 5′‐HM‐FLX, which was identified in urine (Maier‐Salamon et al ., ), was not detectable under the incubation conditions used. After checking the linearity of product formation with time, the enzyme kinetics of 5′‐HM‐FLX formation by pooled HLM was studied in 10 min incubations by varying the concentration of flucloxacillin from 10 to 500 μM.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…The mass increase of 18 relative to flucloxacillin (m/z 454.059) indicates that this product most likely corresponds to the penicilloic acid formed by hydrolysis of the β‐lactam ring of flucloxacillin which is not dependent on CYP‐activity. The penicilloic acid of 5′‐HM‐FLX, which was identified in urine (Maier‐Salamon et al ., ), was not detectable under the incubation conditions used. After checking the linearity of product formation with time, the enzyme kinetics of 5′‐HM‐FLX formation by pooled HLM was studied in 10 min incubations by varying the concentration of flucloxacillin from 10 to 500 μM.…”
Section: Resultsmentioning
confidence: 83%
“…demonstrated that in the 713 human livers analysed, CYP3A4 levels varied markedly, ranging from 0 to 601 pmol·mg −1 protein (Achour et al ., ). This large variability can contribute to the interindividual variability in plasma concentrations of 5′‐HM‐FLX (Maier‐Salamon et al ., ). As mentioned, next to CYP3A4, another CYP, CYP3A7, showed high activity in flucloxacillin hydroxylation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Maier-Salamon et al [10] have reported that the biliary concentration of 5-OH-FX is high and the liver toxicity of FX might be due to the continuously elevated 5-OH-FX. The present docking simulations have shown that the binding affinity of 5-OH-FX to HLA-B*57:01 is significantly high.…”
Section: Resultsmentioning
confidence: 99%